Socially responsible university from the perspective of a student as a stakeholder - a pilot study report = Uczelnia społecznie odpowiedzialna z perspektywy studenta jako interesariusza - komunikat z badania pilotażowego - Spodarczyk, Edyta; Szelągowska-Rudzka, Katarzyna (Zielona Góra: Faculty of Economics and Management Press)
The article presents results and conclusions of a pilot study. This study aimed to determine the importance of distinguishing (model) characteristics for students of SRU, shaping mutual relations with students in five dimensions distinguished by the authors (values, relations, graduate, education, efficient organization) and to indicate the importance of these dimensions by students.
Keywords: uczelnia społecznie odpowiedzialna; student społecznie odpowiedzialny; wymiary społecznej odpowiedzialności; studenci; kształcenie; sprawna organizacja; socially responsible university; socially responsible student; dimensions of the social responsibility; students; education; efficient organization